Technology of creating and using integrated structural and logical schemes in the process of organization of industrial training - Bozhko, N. (Problems of Engineer-Pedagogical Education, 2021)
The article considers the development and application of structural and logical schemes in the educational process. Examples of research on this issue in the works of various scientists are analyzed. The definition of the concept “a structural and logical scheme”, efficiency, advantages and disadvantages of their use in the educational process as well as requirements for their compilation are given in the paper. The role of structural and logical schemes in the organization and implementation of the educational process in terms of training skilled workers is determined. The structure of the teacher's activity in the process of developing structural and logical schemes is characterized; an algorithm of the scheme construction is offered. The use of integrated structural and logical schemes that contain concepts from different disciplines, logically related to each other, in the process of training skilled workers, namely in the organization and implementation of industrial training, allows visualizing the existence of integration links between educational material content, demonstrating these connections to students in class and forming their idea of the integrated application of knowledge gained while studying various disciplines. The concept of "an integrated structural and logical scheme" is introduced. The technology of creating and using integrated structural and logical schemes in the process of the organization of industrial training when preparing future skilled workers for the motor transport industry is developed. The technology is illustrated with the example of an integrated structural and logical scheme created for the topic of industrial training "Marking Works" used in the process of training auto mechanics of the 2nd category. Possibilities of integrated structural and logical schemes in the organization and implementation of industrial training are identified, namely: establishing integration links between industrial training and disciplines of vocational and theoretical training, using them to develop a didactic lesson project and its implementation, using them as visual aids, using them as the basis for various means of training, using them instead of consolidated thematic plans. The technology of developing integrated structural and logical schemes offered in the article is universal and can be applied in the course of training skilled workers of other fields of study.